2022
DOI: 10.1021/acssuschemeng.1c05318
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis-Aided Microbial Biodegradation of High-Density Polyethylene Plastic by Environmental Inocula Enrichment Cultures

Abstract: Polyethylene plastics are a major source of industrial and household wastes, the majority of which end up in the environment or in landfills. These wastes pose challenges for microbial biodegradation due to their polymeric structure. There is a critical need for a process that aids in the breakdown and reuse of plastic compounds. Pyrolysis of high-density polyethylene (HDPE) has previously been used to induce chemical changes in plastic compounds, resulting in more structurally simplistic compounds. Here, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…In our previous study and pyrolysis pilot plant experiments, we demonstrated that the complete dissolution of polyolefin plastics in paraffin wax at a 1:1 (wt) ratio mixture is possible at temperatures over 200 °C, and their viscosities are suitable for flowing the mixture into a pyrolysis reactor. In addition, those prior experiments also demonstrated that both the plastics and the paraffin wax in the mixture were degraded into pyrolysis products (paraffins were converted to alkenes) . In this work here, pyrolysis wax was substituted for the paraffin wax and the results are compared.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…In our previous study and pyrolysis pilot plant experiments, we demonstrated that the complete dissolution of polyolefin plastics in paraffin wax at a 1:1 (wt) ratio mixture is possible at temperatures over 200 °C, and their viscosities are suitable for flowing the mixture into a pyrolysis reactor. In addition, those prior experiments also demonstrated that both the plastics and the paraffin wax in the mixture were degraded into pyrolysis products (paraffins were converted to alkenes) . In this work here, pyrolysis wax was substituted for the paraffin wax and the results are compared.…”
Section: Resultsmentioning
confidence: 91%
“…A unique liquid-phase fast pyrolysis reactor has been designed and fabricated (invention disclosure at Michigan Technological University, Office of Innovation and Commercialization) to control the heat transfer and vapor residence times within the reactor. An earlier paper described the methods of operating the plastic pyrolysis pilot plant . The system is composed of two parts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A unique liquid feed pyrolysis reactor (invention disclosure at Michigan Technological University, Office of Innovation and Commercialization, Houghton, MI, USA) was designed in order to have controllable and rapid heat transfer and tunable vapor residence time within the reactor (Figure 1) [27]. Experimental methods for the pyrolysis system have been described previously by Byrne et al [28] and Kulas et al [27]. The liquid feed was achieved by melting and mixing HDPE obtained from Idaho National Laboratory (research collaborator) with a pyrolysis wax solvent in the dissolution tank at a 1:1 ratio [29].…”
Section: Technology For Pyrolysis Oil Formationmentioning
confidence: 99%